PATRONASE, KLIENTALISME DAN TAHTA PUTRA MAHKOTA PADA PILKADA KOTA KENDARI TAHUN 2017 - Pratama, Rekha Adji (JWP (Jurnal Wacana Politik), 2017)
One of the problems that still occur in local government bureaucracy is patronage and clientelism which is still often used by politicians to carry out a specific agenda outside the main duties and functions of the bureaucracy. This paper aims to determine the forms of patronage and clientelism that is formed in relation politicians, the bureaucrats and the community where the mayor actively "Asrun" using bureaucratic apparatus as a political machine in order to win his son âAdriatma Dwi Putraâ (ADP) as mayor Kendari on the elections simultaneously in 2017. The findings show, the form of patronage and clientelism in this study can be divided into two. First, relations were awakened in the bureaucracy includes determining the scope of careers and positions in the bureaucracy in Kendari, the first form of this is done in order to consolidate the support of the bureaucracy to win ADP. Secondly, relations that built up in the community include the mobilization voice through vote buying and pork barrel. The second form as a strategy to gain support or voice with the way the bureaucratic apparatus into a figure intermediaries to mobilize voice in society.